SDG 2 (Zero Hunger) in the context of the German Sustainable Development Strategy: are we leaving the starving behind? - Sarah Holzapfel; Michael Brüntrup (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The Sustainable Development Goals (SDGs) adopted within the framework of the United Nations' 2030 Agenda are universal and apply to all countries, whereby each country is free to establish its own priorities. In order to address the concern that support for the problems of poverty endemic in developing countries could be curtailed in the process, industrial nations including Germany pledged to link national challenges with international objectives, particularly those relating to poor developing countries – in accordance with the Agenda's principle Leaving no one behind. We analysed the revised version of the “German Sustainable Development Strategy,” (GSDS), adopted on 11 January 2017, which outlines measures designed to implement the 2030 Agenda, with regard to a primary concern of the developing countries, namely goal number 2: ending hunger, achieving food security and improved nutrition, and promoting sustainable agriculture. Specifically, we analysed the indicators, i.e. the strategy's measurable substance. However, the indicators cited in the GSDS fail to incorporate the developing countries' immediate needs. Measures implemented at national level are aimed chiefly at improving ecological sustainability within the context of German agriculture. Here, particular reference is made to two verifiable indicators relating to the propagation of organic farming and the reduction of the nitrogen surplus in the agricultural sector. These objectives are doubtless desirable for Germany, and may make a meaningful contribution towards the achievement of other SDGs (e.g. water, biodiversity, health). However, they hardly contribute to the essence of SDG 2. On the contrary, no account is taken of the possible consequences of these two indicators for food security efforts in developing countries, and, with this, their coherence in terms of development policy. Said consequences could include agricultural extensification and a tendency towards increased food prices. Other policy areas which (could) exercise a considerable influence on global food security, such as bioenergy and agricultural trade, are also overlooked. Although important and necessary measures are described for the international context, which Germany must implement in order to achieve SDG 2, verifiable indicators and commitments that these efforts will be continued in future are lacking. All things considered, the German Sustainable Development Strategy has so far failed to meet the requirements of the 2030 Agenda as regards SDG 2. Which changes are necessary for the further development of the GSDS, planned for 2018? In a national context, an indicator ensuring the (examination of and endeavours to achieve) development coherence in the field of national policy measures surround¬ing SDG 2 is required. As far as the international context is concerned, a credible safeguarding of the current engagements in the field of development cooperation (DC), or a voluntary commit¬ment to increasing the German contribution even after the end of the special initiative “ONE WORLD – No Hunger”, is essential. Indicators concerning the sustainability of German agriculture as a whole, the consumption of agricultural products, specifically animal products, and genetic diversity would be particularly expedient in this regard.
Keywords: 330; Agenda 2030